Nature and Management of Penetrating Craniocerebral Missile Injuries at Shree Birendra Hospital From November 2001 to November 2002 - Sharma, A P (Medical Journal of Shree Birendra Hospital, 2002)
Nature and Management of Penetrating Craniocerebral Missile Injuries at Shree Birendra Hospital From November 2001 to November 2002